Платон или за создавањето имиња - Џукеска, Елена (Филозофски факултет - Скопје, 2016)
2400 years later Plato's discussion on the correctness of the names i.e. on the origin and function of language in "Cratylus" has not ceased to raise questions and answers. The aim of this presentation is by means of linguistic analysis and comparison of this particular dialogue with the other dialogues to investigate Plato's attitude towards language in terms of his own name-making skill. And this skill as the research shows can be viewed both on the level of creation of words and on the level of development of new meanings and it represents significant contribution to the development of the Greek language.
Plato, or on the name-making
Keywords: Plato, names, iconicity